Strengthening the Management of Public Spending in Hungary - Cekota, Jaromir (OECD Economics Department Working Papers, 2002)
This paper analyses the Hungarian public expenditure system and develops policy-oriented recommendations for its improvement. Despite substantial progress achieved in the management of public finances over the 1990s, the level of public expenditure and taxation relative to national income has been comparatively high while the budget process has continued to be driven by short-term considerations and remains input- rather than output-oriented. The government's economic pre-accession programme submitted to the European Commission for the time period 2002-04 needs to be complemented by a thorough public expenditure reform in order to achieve its ambitious targets, implying significant fiscal tightening. This reform entails the development of a medium-term, output-oriented expenditure framework characterised by transparent and comprehensive budget procedures for all fiscal activities of the general government. Effective spending in areas critical for future growth performance -- ...